H-Trend UII in optimizing the halal assurance system in the special region of Yogyakarta - Amal, Muhammad Fakhri; Budiwati , Anisah (Universitas Airlangga, 2025)
This study aims to analyze the opportunities and challenges faced by the Halalan Thoyyiban Research and Education Center (H-Trend) at the Islamic University of Indonesia in optimizing the implementation of the Halal Assurance System in the Special Region of Yogyakarta. H-Trend UII was established as a research institution focusing on the study and investigation of halal products to support the implementation of this regulation. The research employs a qualitative method, collecting data through in-depth interviews with H-Trend UII administrators. The analysis utilizes a SWOT approach to classify the organization's strengths, weaknesses, opportunities, and threats. The findings reveal that H-Trend plays an active role in halal research development through product testing using the RT-PCR method, supporting UMKM (Micro, Small, and Medium Enterprises), and educating the public through the publication of books and brochures. However, several challenges were identified, including limitations in human and financial resources, the wide demographic spread of MSMEs, and the low awareness among business actors regarding the importance of halal certification. This study highlights the potential for H-Trend to be developed into a Halal Assurance Institution (LPH) and a Halal Product Process Assistance Institution (LP3H), thereby expanding its role within the halal ecosystem in the Special Region of Yogyakarta. Keywords: H-Trend UII, Halal Assurance System, MSMEs